\(\left(\dfrac{32}{243}\right)^x=\left(\dfrac{3}{2}\right)^{-1}\)
Tìm \(x\) biết:
\(\left(\sqrt{3}\right)^x=243\)
\(0,1^x=1000\)
\(\left(\dfrac{1}{2}\right)^x=1024\)
\(\left(0,2\right)^{x+3}< \dfrac{1}{5}\)
\(\left(\dfrac{3}{5}\right)^{2x+1}>\left(\dfrac{5}{3}\right)^2\)
\(5^{x-1}+5^{x+2}=3\)
a: \(\left(\sqrt{3}\right)^x=243\)
=>\(3^{\dfrac{1}{2}\cdot x}=3^5\)
=>\(\dfrac{1}{2}\cdot x=5\)
=>x=10
b: \(0,1^x=1000\)
=>\(\left(\dfrac{1}{10}\right)^x=1000\)
=>\(10^{-x}=10^3\)
=>-x=3
=>x=-3
c: \(\left(0,2\right)^{x+3}< \dfrac{1}{5}\)
=>\(\left(0,2\right)^{x+3}< 0,2\)
=>x+3>1
=>x>-2
d: \(\left(\dfrac{3}{5}\right)^{2x+1}>\left(\dfrac{5}{3}\right)^2\)
=>\(\left(\dfrac{3}{5}\right)^{2x+1}>\left(\dfrac{3}{5}\right)^{-2}\)
=>2x+1<-2
=>2x<-3
=>\(x< -\dfrac{3}{2}\)
e: \(5^{x-1}+5^{x+2}=3\)
=>\(5^x\cdot\dfrac{1}{5}+5^x\cdot25=3\)
=>\(5^x=\dfrac{3}{25,2}=\dfrac{1}{8,4}=\dfrac{10}{84}=\dfrac{5}{42}\)
=>\(x=log_5\left(\dfrac{5}{42}\right)=1-log_542\)
\(x^2-19=5.9;\left(2x+1\right)^3=-0,001;\left(\dfrac{5}{6}\right)^{2x-1}=\left(\dfrac{5}{6}\right)^5;\left(\dfrac{1}{3}x-\dfrac{2}{3}\right)^3=27;\left(\dfrac{1}{32}\right)^x=\left(\dfrac{1}{2}\right)^{15}\)
a, \(x^2\) - 19 = 5.9
\(x^2\) - 19 = 45
\(x^2\) = 45 + 19
\(x^2\) = 64
\(x^2\) = 82
\(x\) = 8
b, (2\(x\) + 1)3 = -0,001
(2\(x\) + 1)3 = (-0,1)3
2\(x\) + 1 = -0,1
2\(x\) = -0,1 - 1
2\(x\) = - 1,1
\(x\) = -1,1: 2
\(x\) = - 0,55
\(x^2-19=5\cdot9\\\Rightarrow x^2-19=45\\\Rightarrow x^2=45+19\\\Rightarrow x^2=64\\\Rightarrow x^2=(\pm8)^2\)
\(\Rightarrow\left[{}\begin{matrix}x=8\\x=-8\end{matrix}\right.\)
\(---\)
\((2x+1)^3=-0,001\\\Rightarrow (2x+1)^3=(-0,1)^3\\\Rightarrow2x+1=-0,1\\\Rightarrow2x=-0,1-1\\\Rightarrow2x=-1,1\\\Rightarrow x=-1,1:2\\\Rightarrow x=\dfrac{-11}{20}\\---\)
\(\bigg(\dfrac56\bigg)^{2x-1}=\bigg(\dfrac56\bigg)^5\\\Rightarrow 2x-1=5\\\Rightarrow2x=5+1\\\Rightarrow2x=6\\\Rightarrow x=6:2\\\Rightarrow x=3\\---\)
\(\bigg(\dfrac13x-\dfrac23\bigg)^3=27\\\Rightarrow\bigg(\dfrac13x-\dfrac23\bigg)^3=3^3\\\Rightarrow\dfrac13x-\dfrac23=3\\\Rightarrow\dfrac13x=3+\dfrac23\\\Rightarrow\dfrac13x=\dfrac{11}{3}\\\Rightarrow x=\dfrac{11}{3}:\dfrac13\\\Rightarrow x=11\\---\)
\(\bigg(\dfrac{1}{32}\bigg)^x=\bigg(\dfrac12\bigg)^{15}\\\Rightarrow\bigg(\dfrac{1}{32}\bigg)^x=\bigg[\bigg(\dfrac{1}{2}\bigg)^5\bigg]^3\\\Rightarrow\bigg(\dfrac{1}{32}\bigg)^x=\bigg(\dfrac{1^5}{2^5}\bigg)^3\\\Rightarrow\bigg(\dfrac{1}{32}\bigg)^x=\bigg(\dfrac{1}{32}\bigg)^3\\\Rightarrow x=3\\Toru\)
Tìm x biết:
a) \(\dfrac{-32}{\left(-2\right)^x}=4\) f) \(\left(3x-1\right)^3=\dfrac{-8}{27}\)
b) \(\left(\dfrac{1}{2}\right)^{2x-1}=\dfrac{1}{8}\) g) \(\left(2x+3\right)^2=\dfrac{9}{121}\)
c) \(\dfrac{1}{9}.27^x=3^x\) h) \(5^x+5^{x+2}=650\)
d) \(9^x:3^3=\dfrac{1}{243}\) i) \(\left(x-7\right)^{x+1}-\left(x-7\right)=0\)
e) \(\dfrac{x7}{81}=27\) m) \(\left(\dfrac{-3}{4}\right)^{3x-1}=\dfrac{256}{81}\)
h) \(5^x+5^{x+2}=650\)
\(\Leftrightarrow5^x+5^x.5^2=650\)
\(\Leftrightarrow5^x\left(1+25\right)=650\)
\(\Leftrightarrow5^x.26=650\)
\(\Leftrightarrow5^x=25\)
\(\Leftrightarrow x=2\)
haizzz,đăng ít thôi,chứ nhìn hoa mắt quá =.=
\(\left\{{}\begin{matrix}\dfrac{1}{2}\left(x+2\right)\left(y+3\right)=\dfrac{1}{2}xy+56\\\dfrac{1}{2}\left(x-2\right)\left(y-2\right)=\dfrac{1}{2}xy-32\end{matrix}\right.\)
\(\Leftrightarrow\left\{{}\begin{matrix}\dfrac{1}{2}\left(xy+3x+2y+6\right)=\dfrac{1}{2}xy+56\\\dfrac{1}{2}\left(xy-2x-2y+4\right)=\dfrac{1}{2}xy-32\end{matrix}\right.\)
\(\Leftrightarrow\left\{{}\begin{matrix}3x+2y+6=112\\-2x-2y+4=-64\end{matrix}\right.\)
\(\Leftrightarrow\left\{{}\begin{matrix}3x+2y=106\\-2x-2y=-68\end{matrix}\right.\)
\(\Leftrightarrow\left\{{}\begin{matrix}3x+2y=106\\x=38\end{matrix}\right.\) \(\Leftrightarrow\left\{{}\begin{matrix}x=38\\y=-4\end{matrix}\right.\)
giải phương trình
a) \(5^x=4\)
b) \(5^{2-x}=8\)
c) \(\left(\dfrac{1}{3}\right)^{4+x}=243\)
d) \(\left(\dfrac{2}{3}\right)^x=\dfrac{3}{2}\)
a: \(5^x=4\)
=>\(x=log_54\)
b: \(5^{2-x}=8\)
=>\(2-x=log_58\)
=>\(x=2-log_58\)
c: \(\left(\dfrac{1}{3}\right)^{x+4}=243\)
=>\(3^{-x-4}=3^5\)
=>-x-4=5
=>-x=9
=>x=-9
d: \(\left(\dfrac{2}{3}\right)^x=\dfrac{3}{2}\)
=>\(\left(\dfrac{2}{3}\right)^x=\left(\dfrac{2}{3}\right)^{-1}\)
=>x=-1
Tìm x biết:
\(a,\left(x-\dfrac{3}{4}\right)+50\%=\dfrac{1}{6}\)
\(b,\dfrac{1}{2}x-\dfrac{5}{6}x=\dfrac{7}{2}\)
\(c,\left(4-x\right)\left(3x+5\right)=0\)
\(d,\dfrac{x}{16}=\dfrac{50}{32}\)
\(e,\left(2x-3\right)+\dfrac{3}{2}=-\dfrac{1}{4}\)
a: =>x-3/4=1/6-1/2=1/6-3/6=-2/6=-1/3
=>x=-1/3+3/4=-4/12+9/12=5/12
b: =>x(1/2-5/6)=7/2
=>-1/3x=7/2
hay x=-21/2
c: (4-x)(3x+5)=0
=>4-x=0 hoặc 3x+5=0
=>x=4 hoặc x=-5/3
d: x/16=50/32
=>x/16=25/16
hay x=25
e: =>2x-3=-1/4-3/2=-1/4-6/4=-7/4
=>2x=-7/4+3=5/4
hay x=5/8
Tìm x ∈ N biết :
a) \(8< 2^x\le2^9.2^{-5}\)
b)\(27< 81^3:3^x< 243\)
c)\(\left(\dfrac{2}{5}\right)^x>\left(\dfrac{5}{2}\right)^{-3}.\left(\dfrac{-3}{5}\right)^2\)
\(a,\Rightarrow2^3< 2^x\le2^4\Rightarrow x=4\\ b,\Rightarrow3^3< 3^{12}:3^x< 3^5\\ \Rightarrow3^3< 3^{12-x}< 3^5\\ \Rightarrow12-x=4\Rightarrow x=8\)
Cho mk hỏi :
tìm x,biết
a,\(-3\dfrac{1}{2}\)x -0,75-1,25x=\(\left(\dfrac{-1}{2}\right)^2:\dfrac{-3}{4}+\dfrac{1}{6}\)
b, \(\dfrac{-2}{3}-\left(\dfrac{x}{2}-75\%\right)=\left(\dfrac{3}{-4}-\dfrac{9}{8}\right)^2:\dfrac{-3}{32}-1\dfrac{1}{3}\)
Tìm x thỏa mãn
\(\left(\dfrac{1}{3}\right)^x+\left(\dfrac{1}{3}\right)^{x+2}=\dfrac{10}{243}\)
\(\left(\dfrac{1}{3}\right)^x+\left(\dfrac{1}{3}\right)^{x+2}=\dfrac{10}{243}\)
\(\left(\dfrac{1}{3}\right)^x+\left(\dfrac{1}{3}\right)^x.\left(\dfrac{1}{3}\right)^2=\dfrac{10}{243}\)
\(\left(\dfrac{1}{3}\right)^x.\left[1+\left(\dfrac{1}{3}\right)^2\right]=\dfrac{10}{243}\)
\(\left(\dfrac{1}{3}\right)^x.\dfrac{10}{9}=\dfrac{10}{243}\)
\(\left(\dfrac{1}{3}\right)^x=\dfrac{10}{243}:\dfrac{10}{9}\)
\(\left(\dfrac{1}{3}\right)^x=\dfrac{1}{27}\)
\(\left(\dfrac{1}{3}\right)^x=\left(\dfrac{1}{3}\right)^3\)
\(\Rightarrow x=3\)